Polymorphism in N-(3-Hydroxyphenyl)-3-methoxybenzamide - Sumaya K. Al-Rawe; Daniil Baranov; Agnieszka K. Bronowska; Celine Cano; Michael A. Carroll; Paul G. Waddell (Crystals)
N-(3-hydroxyphenyl)-3-methoxybenzamide was synthesised by amide coupling. After crystallisation, single-crystal X-ray diffraction revealed two distinct polymorphs of the compound: one in the orthorhombic space group Pna21 with one molecule in the asymmetric unit (Z′ = 1) and a second in the triclinic space group P-1 with two molecules in the asymmetric unit (Z′ = 2). A comparison of the structures reveals that the differences between the two can be attributed to conformational variations, disorder, and the dimensionality of the hydrogen bonding networks, with one forming a three-dimensional net and the other forming layers that exhibit approximate p21/b11 layer group symmetry. Molecular dynamics simulations and well-tempered metadynamics-enhanced sampling calculations provide insight into the transition of one polymorph into the other at room temperature. The efficiency of the crystal packing is assessed by a comparison of the densities and melting points of the two structures.